2004
DOI: 10.1212/01.wnl.0000128089.53030.ac
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E controls the risk and age at onset of Parkinson disease

Abstract: The APOE-4 allele increases risk and decreases age at onset of PD, an association that may not be dependent upon cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 35 publications
4
89
0
Order By: Relevance
“…APOE is a confirmed gene that affects the risk and AAO of AD [3] and PD [7]. In addition, the AAO effect of APOE was also confirmed by our previous genomic screen study with a LOD score of 3.28 [9].…”
Section: The Effect On Aao By Snpsupporting
confidence: 62%
“…APOE is a confirmed gene that affects the risk and AAO of AD [3] and PD [7]. In addition, the AAO effect of APOE was also confirmed by our previous genomic screen study with a LOD score of 3.28 [9].…”
Section: The Effect On Aao By Snpsupporting
confidence: 62%
“…Best known as a risk factor for Alzheimer's disease, apoE4 also seems to have a negative impact on the risk, age of onset, progression, or outcome of Parkinson's disease, 15 fronto-temporal dementia, 55 multiple sclerosis, 18 neuromuscular disease, 56 and traumatic brain injury. 16,17 Excitotoxicity has been implicated in all of these conditions, 39,57 whereas increased accumulation of A␤ is seen mainly in Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…8 -11 Three apoE isoforms are found in humans: apoE2, apoE3 (the most common), and apoE4. 12 ApoE4 is associated with increased risk of Alzheimer's disease 13,14 and Parkinson's disease, 15 poor outcome after head injury 16 and stroke, 17 accelerated progression of multiple sclerosis, 18 and subtle neurological impairments in individuals without overt neurological disease. 19,20 Thus, apoE4 may contribute to diverse neurological conditions.…”
mentioning
confidence: 99%
“…190,191 Several recent studies have found the ⑀4 allele to be associated with PD [192][193][194] ; however, an earlier meta-analysis found a marginal association only with the ⑀2 allele. 195 A more consistent association of the ⑀4 allele has been with an increased risk of dementia within a PD sample.…”
Section: Apoementioning
confidence: 99%